IDENTIFIKASI KESULITAN BELAJAR SISWA PADA MATERI IKATAN KIMIA SISWA KELAS XB SMA NEGERI 1 SIANTAN KABUPATEN MEMPAWAH - Anne Mezia (Universitas Muhammadiyah Pontianak, 2018)
The out come of student’s learning achievement are low. Due to there are many student’s did not achieve the minimum competency in Chemical bonding subject because most student’s are not able to understand the problem. This study aimed to find out the difficulties and the factors that cause learning difficulties of students at chemical bonding’s subject in class X-B SMA Negeri 1 Siantan, Mempawah District. This research was a descriptive study with qualitative approach case study, the population of class X with a sample of 35 people in class X-B. Data collection technique used indirect communication techniques (questionnaire), direct communication (interview), post-test and documentation, while the data collection toolused the pre-test, questionnaire sheet and the interview’s result. The result showed that students have learning difficulties in determining the ionic bonds’ topic which amountof 62.85%, 55.71% in covalent bonds’ topic and coordinate covalent bonds’ topic which of 85.71%. Internal factors that affect students' learning difficulties was aspects of motivation with effort indicators to learn chemical bonding and attention of students towards learning the materials of Chemical bonding with the percentage of influence each by 58.18%, while external factors that affected learning difficulties of Chemical bonding subject were the teaching methods of the teacher with a percentage of 60.00%. The conclusions showed that there were difficulties of student’s learning in chemical bonding material and there were external either internal factors influence the students’ ability learning.